Merekonstruksi Candi Terkubur: Studi Kasus: Eskavasi dan Pemugaran Candi Kimpulan di Universitas Islam Indonesia (UII) - Ahmad Saifudin Mutaqi; Robert Rianto Wijaya (ATRIUM: Jurnal Arsitektur, 2023)
Title: Reconstructing the Buried Temple Case Study: Candi Kimpulan Excavation and Restoration at Universitas Islam Indonesia (UII)   The discovery of the archaeological site, Candi Kimpulan, during the foundation excavation of the Central Library Building at Universitas Islam Indonesia (UII) in December 2009 halted the ongoing construction. The agreement to conduct the restoration of this ancient site raised concerns about the duration and required space for the restoration process. Moreover, complications arose due to the location of the artifact discovery directly beneath the construction site. This article presents a literature review of various scholarly journals directly related to the reconstruction of buried temple structures. It aims to provide insights into the temple reconstruction process amid a comprehensive redesign of the university's library building. The study reveals crucial factors that significantly influenced the successful and relatively swift completion of the Candi Kimpulan restoration project. This endeavor serves as a positive benchmark for similar cases of buried temple discoveries, offering valuable lessons in planning and executing restoration projects.